1987
DOI: 10.1029/ja092ia03p02565
|View full text |Cite
|
Sign up to set email alerts
|

On calculating ionospheric conductances from the flux and energy of precipitating electrons

Abstract: Auroral zone conductances can be estimated from the energy flux and average energy of precipitating electrons. These estimates are based on the assumption that the conductances produced by the electrons are very similar to those produced by electrons with Maxwellian energy distributions having the same energy flux and average energy. There has been some confusion in the application of this method because for a Maxwellian the average energy is twice the characteristic energy or temperature. We present revised e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
549
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(585 citation statements)
references
References 9 publications
17
549
3
Order By: Relevance
“…With these quantities defined, equation (7) can be solved for the electric field tangential to the poleward arc, E t , and all characteristic parameters of the arc and the ionospheric dissipation can be calculated as outlined in Appendix A. The Cowling conductivity follows from empirical relations with the electron energy flux and mean energy after Robinson et al [1987].…”
Section: Poleward Arc Of the Auroral Bulgementioning
confidence: 99%
See 1 more Smart Citation
“…With these quantities defined, equation (7) can be solved for the electric field tangential to the poleward arc, E t , and all characteristic parameters of the arc and the ionospheric dissipation can be calculated as outlined in Appendix A. The Cowling conductivity follows from empirical relations with the electron energy flux and mean energy after Robinson et al [1987].…”
Section: Poleward Arc Of the Auroral Bulgementioning
confidence: 99%
“…Calculation of the ionospheric electric field and dissipation needs calculation of Pedersen and Hall conductivities. They can be obtained from _ W arc and F k by employing the empirical expressions of Robinson et al [1987].…”
Section: Appendix Amentioning
confidence: 99%
“…Brekke et al [1974] suggested that the ratio of heightintegrated Hall conductivity to height-integrated Pedersen conductivity would scale as electron energy, and Robinson et al [1987] provide a prescription for calculating characteristic energy for assumed Maxwellian precipitation as a function of S H /S P .…”
Section: First-stage Conductance Ratio Filteringmentioning
confidence: 99%
“…The ionospheric dissipation is now modeled using the formulation of Robinson et al [1987]. It would be a …”
Section: Low-dimensional Modelmentioning
confidence: 99%